Acute Care Surgery in Heart Transplant Recipients. Issue 10 (October 2013) - Ashman, Zane; Lancaster, Elizabeth; Satou, Nancy; Shemin, Richard J.; Hiatt, Jonathan R.; Benharash, Peyman
Orthotopic heart transplantation (OHT) is the optimal treatment for end-stage heart failure. We reviewed our institutional experience between 2008 and 2012 with acute care surgery (ACS) consultations and procedures within 1 year of OHT in recipients bridged to transplantation with medical therapy (MT, n = 169), including intravenous inotropes, and ventricular assist devices (VADs, n = 74). In total, 28 consultations were required in 21 patients (9%) and 16 procedures were performed in 11 patients (5%). The interval from transplantation to consultation was shorter for the MT group (50 vs 82 days; P = 0.015), whereas the interval from consultation to operation was longer (5 vs 1 day; P = 0.03). Patients undergoing MT were more likely to require consultation for abdominal problems (88 vs 27%; P = 0.004). All but one of the seven ischemic/inflammatory abdominal problems occurred in the MT group. Complications occurred after five ACS procedures (31%) in two patients undergoing MT and three patients undergoing VAD. Mortality was 24 per cent with five deaths occurring within 30 days of ACS consultation and/or operation. In summary, this is one of the largest series of ACS problems in patients undergoing OHT bridged to transplant with MT or VAD. With similar incidence in MT and VAD groups, ACS consultations and operations are infrequent with high mortality and morbidity.